Former au numérique éducatif : les conceptualisations des formateurs - Jonathan Rappe; Aurélien Fiévez
Though teaching practices integrating digital technology are well documented in the scientific literature, the matter of their initial training is not. In this case study, we explore, through field observations, self-confrontation interviews and interpretative analysis, two trainers' activity in this training area. To do so, we use the conceptualization in action theoretical framework (Pastré, 2011; Vergnaud, 1996). Results show similarities and differences not only between training actions but also in conceptualizations that seem to guide those actions in the trainers' practice. Those differences, revealed by the activity analysis, tend to show that a similar didactical approach will be led differently according to the way the trainer has conceptualized teaching, educative use of digital tools and teachers' training.